An Analysis of Factors Influencing the Students’ Phonemic Awareness in Speaking Activities - Sari, Mayang; Noni, Nurdin; Korompot, Chairil (BATARA DIDI : English Language Journal, 2024)
This research used descriptive quantitative method. The sample consisted of 18 participants from MA Al Hidayah Bakke. The objective of the research is to find out the factors influencing the students’ phonemic awareness by carrying out questionnaire. In this research, there were four factors influencing the students’ phonemic awareness in speaking activity such as practicing time, language difference, motivation, and phoneme teaching and learning in the school. The result shows that as EFL learners there are four factors influence the students’ phonemic awareness such as practicing time is categorized as sufficient factor, language difference is categorized as strong factor, motivation is categorized as strong factor and phoneme teaching and learning is categorized as strong factor.